Financial Development and Growth in the Caucasus and Central Asia - Poghosyan, Tigran (IMF Working Papers; Working Paper ;, 2022)
This paper presents stylized facts on financial development in the CCA countries relative to their EM and LIC peers and assesses how financial development can boost growth in the CCA. Drawing on IMF's multidimensional index of financial development, we find that CCA countries have made progress following the independence in early 1990s. However, the progress was uneven across the CCA, resulting in a divergence of financial development over time and mixed performance relative to EM and LIC peers. Financial institutions have progressed the most, while financial markets remain underdevelped in most CCA countries except Kazakhstan. In terms of sub-indicators of financial development, financial access has expanded markedly, while the depth of financial intermediation has remained largely shallow and efficiency of financial intermediation has fluctuated over time. Standard growth regressions suggest that CCA countries with relatively lower level of financial development have scope to boost annual growth rates between 0.5-2.5 percent by reaching the level of financial development of frontier CCA countries.